Basicity determination of SBA-15 doped with different alkaline metals through CO₂ adsorption and isopropanol decomposition - Reale, Natalia Romina (2020)
In order to increase the activity and selectivity towards to light olefins in the Fischer-Tropsch synthesis, new support for the role of iron (Fe) are presented. Thus, SBA-15 was synthetized and doped with different alkaline metals preserving the structural characteristics of the mesoporous solid. The samples were characterized by X-ray diffraction at low angles, N₂ adsorption, atomic absorption spectroscopy, CO₂ desorption at programmed temperature and isopropanol test. The alkaline metals (Li, K and Cs) introduction into the channels of the solid, generate basic sites of different strength that are not present in the SBA-15 without doping and do not produce significant changes in the structural and textural properties of the SBA-15, only a densification in the walls of the channels is evidenced. According to the alkaline metal used and through CO₂ adsorption and isopropanol decomposition, it was possible to established the order by the total number of sites: Li >> K ≈ Cs, and the force order for both types of sites (weak and intermediate): Li > Cs > K.